Pendampingan Literasi dan Numerasi Digital Berbasis Komunitas melalui Integrasi Kearifan Lokal Papua bagi Anak di Wilayah Pesisir Biak Timur - Muslim Lobubun; Roma Firmansyah; Putri Anugraheli Ramba Orun (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Limited access to engaging learning resources, inadequate use of digital technology, and the underutilization of local wisdom continue to hinder the development of children's literacy and numeracy skills in coastal communities. This community service program aimed to improve children's reading, writing, and numeracy skills through community-based mentoring that integrates digital learning media with Papuan local wisdom. The program was implemented in the coastal area of East Biak District, Biak Numfor Regency, using a Participatory Action Research (PAR) approach involving 50 early childhood participants and 30 members of the PAR SM Karmel Bosnik community as local partners. The activities included needs assessment, training on digital learning media, eight mentoring sessions, and program evaluation using pre-tests, post-tests, classroom observations, and paired-sample t-tests. The results demonstrated substantial improvements in reading (96%), writing (36.8%), and numeracy (10%), with statistical analysis confirming significant gains across all assessed competencies after the intervention. In addition, the program strengthened the capacity of community partners to implement interactive, technology-supported, and culturally contextualized learning practices. These findings indicate that community-based mentoring integrating digital media and Papuan local wisdom is an effective strategy for strengthening children's literacy and numeracy skills in coastal areas and has strong potential for adaptation in communities with similar educational contexts.